Epstein–Barr Virus Neuroretinitis in a Lung Transplant Patient. Issue 1 (March 2017) - Hsia, Yen C.; Chin-Hong, Peter V.; Levin, Marc H.
Abstract : Abstract: Epstein–Barr virus (EBV)-associated optic neuropathy is rare with few reported cases, mostly involving immunocompetent patients who developed optic nerve involvement after infectious mononucleosis. We describe a unique case of a patient who developed severe bilateral EBV neuroretinitis after solid organ transplant.